2014
DOI: 10.1017/s0954579414001084
|View full text |Cite
|
Sign up to set email alerts
|

Regulating sadness and fear from outside and within: Mothers' emotion socialization and adolescents' parasympathetic regulation predict the development of internalizing difficulties

Abstract: Multilevel models of developmental psychopathology implicate both characteristics of the individual and their rearing environment in the etiology of internalizing problems and disorders. Maladaptive regulation of fear and sadness, the core of anxiety and depression, arises from the conjoint influences of ineffective parasympathetic regulation of emotion and ineffective emotion socialization experiences. In 171 youths (84 female, M = 13.69 years, SD = 1.84), we measured changes of respiratory sinus arrhythmia (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 87 publications
(119 reference statements)
2
55
1
Order By: Relevance
“…It is in keeping with more recent conceptualizations and research on family interactions, transactions, and relationships (Kuczynski & Parkin, 2007) to include the important role of offspring influences on others as well as on their own development (Hastings, Zahn-Waxler, Robinson, Usher, & Bridges, 2000; Hastings, Klimes-Dougan, Kendziora, Brand, & Zahn-Waxler, in press; Zahn-Waxler, 2010). Adolescence is a time period when the impact of offspring is increased due in part to expanding self-awareness, search for autonomy, and establishment of personhood.…”
Section: Discussionmentioning
confidence: 70%
“…It is in keeping with more recent conceptualizations and research on family interactions, transactions, and relationships (Kuczynski & Parkin, 2007) to include the important role of offspring influences on others as well as on their own development (Hastings, Zahn-Waxler, Robinson, Usher, & Bridges, 2000; Hastings, Klimes-Dougan, Kendziora, Brand, & Zahn-Waxler, in press; Zahn-Waxler, 2010). Adolescence is a time period when the impact of offspring is increased due in part to expanding self-awareness, search for autonomy, and establishment of personhood.…”
Section: Discussionmentioning
confidence: 70%
“…Similar to the adult literature, studies of children with anxiety disorders have suggested lower PNS functioning at baseline (Dieleman et al 2015). Studies employing emotional regulation or trauma recall tasks in adolescents with anxiety disorders have shown no differences in RSA responsivity (Fisher and Newman 2013; Shenk et al 2014; Kirsch et al 2015) or have found differences in female, but not male adolescents (Hastings et al 2014). To date, there have been no studies employing the TSST in pubertal adolescents with anxiety disorders using RSA as an outcome measure.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, genetic variants associated with heritable variation in vagal control of autonomic function have been identified (Nolte et al , 2017), and previous studies suggest that, e.g. maternal supportive emotion socialization is linked to vagal activity during active emotion regulation in youth (Hastings et al , 2014). …”
Section: Discussionmentioning
confidence: 99%